2022
DOI: 10.32604/cmc.2022.020044
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches to Detect DoS and Their Effect on WSNs Lifetime

Abstract: Energy and security remain the main two challenges in Wireless Sensor Networks (WSNs). Therefore, protecting these WSN networks from Denial of Service (DoS) and Distributed DoS (DDoS) is one of the WSN networks security tasks. Traditional packet deep scan systems that rely on open field inspection in transport layer security packets and the open field encryption trend are making machine learning-based systems the only viable choice for these types of attacks. This paper contributes to the evaluation of the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Each session consumes a unique communication duration based on the currently available communicating parties in the network [ 60 ]. As given in Figure 8 , the IHF production latency varies from 110 milliseconds (msec) to 155 msec.…”
Section: Resultsmentioning
confidence: 99%
“…Each session consumes a unique communication duration based on the currently available communicating parties in the network [ 60 ]. As given in Figure 8 , the IHF production latency varies from 110 milliseconds (msec) to 155 msec.…”
Section: Resultsmentioning
confidence: 99%
“…Wazirali and Ahmad [19] evaluated the effectiveness of machine learning classification algorithms in detecting (1) flooding, (2) gray hole, and (3) black hole distributed denial of service attacks in wireless sensor networks. We conducted our review using a WSNbased dataset, referred to as WSN-DS, and took the accuracy and speediness measures into account.…”
Section: Related Workmentioning
confidence: 99%
“…The authors also found that one of the best machine learning techniques for protecting wireless sensor networks from DoS is the decision tree with a 100% accurate result. Moreover, the authors in [115] analyzed the effect of different ML algorithms for DoS detection in WSNs. They chose ML algorithms of different types (statistical, logical, instance, and deep learning) and applied them to different dataset sizes to study the effect of data volume on the training process in ML algorithms.…”
Section: Intrusion Detectionmentioning
confidence: 99%